Designing and collecting data for a longitudinal study: the Sleman Health and Demographic Surveillance System (HDSS). Issue 7 (November 2018) - Dewi, Fatwa S.T.; Choiriyyah, Ifta; Indriyani, Citra; Wahab, Abdul; Lazuardi, Lutfan; Nugroho, Agung; Susetyowati, Susetyowati; Harisaputra, Rosalia K.; Santi, Risalia; Lestari, Septi K.; NG, Nawi; Hakimi, Mohammad; et al.
Background: This paper describes the methodological considerations of developing an urban Health and Demographic Surveillance System (HDSS), in the Sleman District of Yogyakarta, Indonesia. Methods: 1) The Sleman District was selected because it is mostly an urban area. 2) The minimum sample size was calculated to measure infant mortality as the key variable and resulted in a sample of 4942 households. A two-stage cluster sampling procedure with probability proportionate to size was applied; first, 216 Censuses Blocks (CBs) were selected, and second, 25 households in each CB were selected. 3) A baseline survey was started in 2015, and collected data on demographic and economic characteristics and verbal autopsy (VA); the 2nd cycle collected updated demographic data, VA, type of morbidity (communicable and non-communicable diseases, disability and injury) and health access. 4) The data were collected at a home visit through a Computer-Assisted Personal Interview (CAPI) on a tablet device, and the data were transferred to the server through the Internet. 5) The quality control consisted of spot-checks of 5% of interviews to control for adherence to the protocol, re-checks to ensure the validity of the interview, and computer-based data cleaning. 6) A utilization system was designed for policy-makers (government) and researchers. Results: In total, 5147 households participated in the baseline assessment in 2015, and 4996 households participated in the second cycle in 2016 (97.0% response rate). Conclusions: Development of an urban HDSS is possible and is beneficial in providing data complementary to the existing demographic and health information system at local, national and global levels.